EFEKTIVITAS PBL BERBANTUAN AUDIOVISUAL TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 3 BOTUPINGGE - Paneo, Nur Ain; Abdul Haris Panai; Kudus; Meylan Saleh; Rifda Mardian Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem in this study is whether the implementation of the Problem-Based Learning (PBL) model supported by audio-visual media can improve students’ learning outcomes in the IPAS (Integrated Science and Social Studies) subject in Grade V of SDN 3 Botupingge. This study aims to enhance students’ learning outcomes through the application of the Problem-Based Learning model assisted by audio-visual media in the IPAS subject. The research method employed was Classroom Action Research (CAR), utilizing data collection techniques such as observation, interviews, tests, and documentation. The subjects of this study were 23 fifth-grade students of SDN 3 Botupingge. The results indicated that in Cycle I, of the 23 students उपस्थित, the percentage of students who achieved mastery learning was 34.78%. In Cycle II, the percentage significantly increased to 91.70%. The predetermined success indicator, namely that at least 75% of students achieve mastery learning, was successfully attained. It can be concluded that the implementation of the Problem-Based Learning model assisted by audio-visual media effectively improves students’ learning outcomes in the IPAS subject in Grade V of SDN 3 Botupingge.